Structure and properties of CdS thin films prepared by pulsed laser assisted chemical bath deposition. (November 2016) - Garcia, L.V.; Loredo, S.L.; Shaji, S.; Aguilar Martinez, J.A.; Avellaneda, D.A.; Das Roy, T.K.; Krishnan, B.
Graphical abstract: Highlights: ⿢ CdS thin films were deposited by normal CBD and pulsed laser assisted CBD. ⿢ Characterized these films using XRD, Raman, XPS, AFM, optical and electrical measurements. ⿢ Accelerated growth was observed in PLACBD process with interesting morphologies. ⿢ Better conductivity and photocurrent response observed for the PLACBD CdS. Abstract: Cadmium sulphide (CdS) is a well known n-type semiconductor having suitable optoelectronic properties for solar cell applications. In the present work, we report the preparation and characterization of CdS thin films by pulsed laser assisted chemical bath deposition (PLACBD). CdS thin films were synthesized from a chemical bath containing cadmium chloride, triethanolamine, ammonium hydroxide and thiourea at different conditions. The thin films were prepared by in situ irradiation of the chemical bath using a Q-switched Nd:YAG laser with two different output wavelengths (532 nm and 1064 nm). The thin films deposited for 10, 15 and 20 min were characterized by X-ray diffractometry (XRD), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), Atomic force microscopy (AFM), UV⿿vis absorption spectroscopy and photoconductivity measurements. Our results showed that in-situ irradiation of the chemical bath using pulsed laser resulted accelerated growth of the CdS thin films.